Protective neutralizing epitopes in SARS‐CoV‐2 - Liu, Hejun; Wilson, Ian A. (Immunological reviews, 2022)
The COVID‐19 pandemic has caused an unprecedented health crisis and economic burden worldwide. Its etiological agent SARS‐CoV‐2, a new virus in the coronavirus family, has infected hundreds of millions of people worldwide. SARS‐CoV‐2 has evolved over the past 2 years to increase its transmissibility as well as to evade the immunity established by previous infection and vaccination. Nevertheless, strong immune responses can be elicited by viral infection and vaccination, which have proved to be protective against the emergence of variants, particularly with respect to hospitalization or severe disease. Here, we review our current understanding of how the virus enters the host cell and how our immune system is able to defend against cell entry and infection. Neutralizing antibodies are a major component of our immune defense and have been extensively studied for SARS‐CoV‐2 and its variants. Structures of these neutralizing antibodies have provided valuable insights into epitopes that are protective against the original ancestral virus and the variants that have emerged. The molecular characterization of neutralizing epitopes as well as epitope conservation and resistance are important for design of next‐generation vaccines and antibody therapeutics.